Logistics Trends 2020: A National Delphi Study Concerning the German Logistics Sector - Stephan Zelewski; Alessa Münchow-Küster; René Föhring (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
The logistics sector is subject to profound changes that are caused by techno-logical innovations as well as by structural changes in the implementation of logistics business processes. Therefore, it is important for companies to recognize such changes in an early stage and to prepare for them strategically. This applies not only for directly concerned logistics service providing companies, but also for forwarders in general. Within a Delphi study, a team of the University Duisburg-Essen researched pioneering changes in the logistics sector and the underlying change driving forces. Over one hundred logistics experts from economy, science and politics have been systematically questioned about future logistics trends with the help of an online questionnaire. The survey stretched over four rounds in total with Delphi-typical quantitative and qualitative feedback for the participants. Altogether, about 500 hypothetical logistics trends - of organizational-conceptual as well as of technological kind - have been identified and evaluated regarding their economical relevance. At the end of the Delphi study, 10 organizational-conceptual and additional 10 technological essential logistics trends emerged. They were carefully examined in three dimensions: probability of occurrence, desirability of occurrence and impact on the logistics sector. The key results of this current Delphi study will be presented and commented from a business point of view. Action fields important for a strategic positioning of logistics companies in their future competitive environments will be illustrated in particular.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; delphi study; empirical research; logistics trends; online survey